Integration of identity and emotion information in faces: fMRI evidence - Yankouskaya, A; Stolte, M; Moradi, Z; Rotshtein, P; Humphreys, G (Elsevier, 2017)
Separate neural systems have been implicated in the recognition of facial identity and emotional expression. A growing number of studies now provide evidence against this modular view by demonstrating that integration of identity and emotion information enhances face processing. Yet, the neural mechanisms that shape this integration remain largely unknown. We hypothesize that the presence of both personal and emotional expression target information triggers changes in functional connectivity between frontal and extrastriate areas in the brain. We report and discuss three important findings. First, the presence of target identity and emotional expression in the same face was associated with super capacity and violations of the independent processing of identity and expression cues. Second, activity in the orbitofrontal cortex (OFC) was associated with the presence of redundant targets and changes in functional connectivity between a particular region of the right OFC (BA11/47) and bilateral visual brain regions (the inferior occipital gyrus (IOG)). Third, these changes in connectivity showed a strong link to behavioural measures of capacity processing. We suggest that the changes in functional connectivity between the right OFC and IOG reduce variability of BOLD responses in the IOG, enhancing integration of identity and emotional expression cues in faces.